Frank O’Connor at Work - Steinman, Michael. author. aut Link
XII, 163 p.
Keywords: Frank O'Connor was a most painstaking writer, sometimes taking up to ten years to revise and polish a story. This book attempts to examine the process and tries to reveal something about O'Connor's perception of his craft and the environment from which his art emerged.